The development of sports: A comparative analysis of the early institutionalization of traditional sports and E-Sports - Summerley, R. (Games and Culture, 2020)
This article takes the definition of a sport as "an institutionalized game" under which both "traditional sports" and "E-sports" fall. It takes a comparative analytical approach that examines the historical documentation and cultural output of thesetwo major categories of sports and their early institutionalization. Given the increasing interest in, engagement with and spectator numbers of E-sports, it is worth considering the key similarities and differences between various institutions.This article examines traditional sports institutions from the mid-19th to late19th century alongside E-sports institutions that emerged from the mid-1990s to the present day. Firstly, the processes of institutionalization are analyzed with these examples in mind and, secondly, are compared to draw out the significant differences and similarities between the factors affecting early institutionalization.